EFEKTIVITAS PENGGUNAAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) DI MTs MUHAMMADIYAH KAJAI - Kasih Hayati; Muhiddinur Kamal; Iswantir M; Wedra Aprison (Universitas Pahlawan Tuanku Tambusai, 2022)
The use of methods in a teaching and learning process is very helpful for teachers and students. Because the method is a structured way in the teaching and learning process to achieve the goals of the teaching and learning process itself. Because with it, it has a big influence in supporting learning success, because through the method learning material can be more easily conveyed. The purpose of this trial is to prove the effectiveness of the role playing method in improving learning outcomes. The research method used in this study is experimental, quasi-experimental design and the research design is a non-equivalent control group design that takes two classes directly. This research was conducted at MTs Muhammadiyah Kajai. The researched is all class VIII. There are two classes used, namely as an experimenter and a controller. The sampling was done by random sampling (Probability Sampling), the sample in this study was class VIII, amounting to 48 people. Class VIII A as an experimental class, which is a class taught by the role playing method, and class VIII B as a control class or a class taught by the lecture method. The instrument used in this study was a test of learning outcomes in the form of multiple choice questions and observation sheets. The data technique in this study used descriptive and inferential statistical analysis. Descriptively explained that the control class obtained 63,375. While the experimental class obtained 81,167 and deductively the value of t_count is 5,675 and t_table is 2,01290, and the significance is 0.000. This study concludes that the hypothesis is accepted. The application of the role playing method is effective to improve student learning outcomes in the subject of Islamic Cultural History at MTs Muhammadiyah Kajai. Keywords: Effectiveness, Role Playing Method, Learning Outcomes, History of Islamic Culture